Innate Immunity and Pathogenesis of Biliary Atresia - Ortiz-Perez, Ana; Donnelly, Bryan; Temple, Haley; Tiao, Greg; Bansal, Ruchi; Mohanty, Sujit Kumar (Frontiers in Immunology, 2020)
Biliary atresia (BA) is a devastating fibro-inflammatory disease characterized by the obstruction of extra-hepatic and intra-hepatic bile ducts in infants that can have fatal consequences, when not treated timely. It is the most common indication of pediatric liver transplantation worldwide and the development of new therapies, to alleviate the need of surgical intervention, has been hindered due to its complexity and lack of understanding of the disease pathogenesis. For that reason, significant efforts have been made towards development of experimental models and strategies to interrogate, and understand the etiology and disease mechanisms to identify novel therapeutic targets. The only characterized model of BA, using a Rhesus Rotavirus Type A infection of newborn BALB/c mice, have enabled the identification of key cellular and molecular targets involved in epithelial injury and duct obstruction. However, the establishment of an unleashed chronic inflammation followed by a progressive pathological wound healing process remains poorly understood. Similar to T cells, macrophages can adopt different functional programs (pro-inflammatory (M1) and resolutive (M2) macrophages) and influence the surrounding cytokine environment and the cell response to injury. In this review, we provide an overview of the immunopathogenesis of BA and discuss the implication of innate immunity in the disease pathogenesis, and highlight their suitability as therapeutic targets.